2016
DOI: 10.1155/2016/3219276
|View full text |Cite
|
Sign up to set email alerts
|

SSR Mapping of QTLs Conferring Cold Tolerance in an Interspecific Cross of Tomato

Abstract: A population of 146 RILs (Recombinant Inbred Line) was derived from the cross between a cold-sensitive cultivated Solanum lycopersicum L. XF98-7 and a cold-tolerant wild Solanum pimpinellifolium LA2184. Relative germination ratio (RGR) and chilling index (CI) were used to evaluate the cold tolerance of the parental lines and RILs. It was found that the RGR and CI were significantly different between S. lycopersicum XF98-7 and S. pimpinellifolium LA2184 under cold treatment, indicating that wild species was mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…map function of RQTL). The number of markers is similar or higher compared to other recent publications that determined QTL in tomato (Liu et al 2016;Wen et al 2019).…”
Section: Genotyping Of the Ril Populationssupporting
confidence: 75%
“…map function of RQTL). The number of markers is similar or higher compared to other recent publications that determined QTL in tomato (Liu et al 2016;Wen et al 2019).…”
Section: Genotyping Of the Ril Populationssupporting
confidence: 75%
“…Although QTLs linked to low temperature tolerance have been reported in many plants like tomato [130], Rice [131], wheat [33]; However in cotton studies related to identification of QTLs for freezing tolerance are scanty.…”
Section: Qtls For Freezing Tolerancementioning
confidence: 99%
“…Similarly, there was no relationship between salt tolerance at the germination and seedling stages in a comprehensive study involving over 6,000 barley cultivars from diverse regions (Mano et al, 1996). There were similar problems with chilling stress studies in early plant development; no correlation was observed between the germination and seedling stage in rice (Oryza sativa) and tomato (Solanum lycopersicum) under cold stress (Wang et al, 2011;Ranawake et al, 2014;Liu et al, 2016). In contrast, Liu (1994) concluded that the degree of chilling tolerance during germination was consistent with that at the seedling stage.…”
Section: Discussionmentioning
confidence: 99%